TINJAUAN YURIDIS TERHADAP STATUS ANAK PERUSAHAAN YANG INDUK PERUSAHAAN BERUBAH STATUS MENJADI PENANAMAN MODAL ASING - CHRISTINAWATY CHRISTINAWATY (PREMISE LAW JURNAL, 2015)
Foreign investment indicates that a motive of a company to invest its capital in a certain country is to obtain profit. The profit comes from several factors such as low workers’wage and selling raw materials for finished products.meanwhile the country which receives the capital expects the participation of of the investor to develop its national development. However it usually faces problem about the status of subsidiary company when holding company gets the facility of PMA (foreign investment). Law of investment as the legal means of foreign investment in Indonesian doesn’t clearly regulate in detail the status of subsidiary company. This problem become the basic thinking for the researcher to conduct a research , based on judicial point of view . on the status of subsidiary company with its holding company changed to foreign investment. Keywords : status of subsidiary company